Kegiatan Bersih-bersih dan Gotong Royong sebagai Upaya Meningkatkan Kebersihan Lingkungan di Desa Sakra Selatan, Lombok Timur - Husnul Wadi; M. Soalihin; Safnowandi Safnowandi; Iwan Doddy Dharmawibawa (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
Environmental cleanliness is one of the important factors in realizing a healthy and sustainable quality of life for the community. Low concern for environmental cleanliness can cause various problems, such as garbage buildup, blockage of drainage channels, and increased risk of environment-based diseases. This community service activity aims to increase community awareness and participation in maintaining environmental cleanliness through cleaning and mutual cooperation activities in South Sakra Village, East Lombok Regency. The method used is a participatory approach with stages of preparation, implementation, and evaluation. The activity involved the village government, community leaders, youth, and local residents in road sweeping activities, garbage collection and transportation, cleaning drainage channels, weed cutting, and arranging public facilities. The results of the activity showed an improvement in the quality of environmental cleanliness which was characterized by reduced waste, improved drainage channel function, and a neater and more comfortable environment. In addition, this activity also increases community participation, strengthens social solidarity, and fosters a sense of shared responsibility in maintaining the cleanliness of the environment. However, the sustainability of the results of activities requires support in the form of regular mutual cooperation, waste management education, and continuous coordination from the village government. Thus, cleaning activities and mutual cooperation are effective strategies in improving the quality of the environment while strengthening community empowerment, and have the potential to be replicated in other areas with similar characteristics.